Diallyl Trisulfide Causes Male Infertility with Oligoasthenoteratospermia in Sitotroga cerealella through the Ubiquitin–Proteasome Pathway - Sakhawat Shah; Karam Khamis Elgizawy; Meng-Ya Wu; Hucheng Yao; Wen-Han Yan; Yu Li; Xiao-Ping Wang; Gang Wu; Feng-Lian Yang (Cells, 2023)
Essential oils extracted from plant sources along with their biologically active components may have negative effects on insects. Diallyl trisulfide (DAT) is an active component of garlic essential oil, and it exhibits multi-targeted activity against many organisms. Previously we reported that DAT induces male infertility and leads to apyrene and eupyrene sperm dysfunction in Sitotroga cerealella. In this study, we conducted an analysis of testis-specific RNA-Seq data and identified 449 downregulated genes and 60 upregulated genes in the DAT group compared to the control group. The downregulated genes were significantly enriched in the ubiquitin–proteasome pathway. Furthermore, DAT caused a significant reduction in mRNA expression of proteasome regulatory subunit particles required for ATP-dependent degradation of ubiquitinated proteins as well as decreased the expression profile of proteasome core particles, including β1, β2, and β5. Sperm physiological analysis showed that DAT decreased the chymotrypsin-like activity of the 20S proteasome and formed aggresomes in spermatozoa. Overall, our findings suggest that DAT impairs the testis proteasome, ultimately causing male infertility characterized by oligoasthenoteratospermia due to disruption in sperm proteasome assembly in S. cerealella.